“We Can Do Anything but We Can't Do Everything”: Exploring the Perceived Impact of International Pediatric Programs on U.S. PICUs - Berkman, Emily R.; Clark, Jonna D.; Diekema, Douglas S.; Lewis-Newby, Mithya (Frontiers in Pediatrics, 2019)
Purpose: Every year, an increasing number of international patients seek medical care in the United States (U.S.), yet little is known about their impact. Based on single institution experiences, we wanted to explore the perceived impact of international pediatric patients on large academic U.S. pediatric intensive care units (PICUs), as they are already taxed systems. Methods: To explore current perceptions, seven geographically diverse institutions who advertise care for international patients on their websites and have ≥24 PICU beds were identified after IRB approval was obtained. We consented and interviewed PICU division chiefs or medical directors from each institution regarding their demographics and international patients. Common themes were identified. Results: Participating institutions were diverse in geographic location, census, and resource allocation strategies. Five of the seven institutions reported the presence of a formal international patient program. Four of those five reported an increase in international patients receiving PICU care over the past five years. International patients sought complex surgeries, advanced cancer treatments and metabolic/genetic evaluations. We identified three primary domains that require further exploration and research: 1) cultural and language differences leading to barriers in providing optimal care to international patients 2) institutional financial considerations, and 3) perceived positive and negative impact on the care of local/domestic patient populations. Conclusions: The presence of international programs raises a number of important ethical questions, including whether clinicians have a greater duty to serve residents of the local community as opposed to international patients when resources are limited. Further exploration is warranted.